(untitled) (Research, Society and Development, 2023)
This paper examines the agribusiness influence on Brazilian politics and how it has affected the country’s foreign policy agenda. The method used is discourse analysis. More specifically, we rely on Maarten Hajer’s concept of storylines, developed in his influential book The Politics of Environmental Discourse (1995). The purpose is to analyze how ruralist storylines, reshaped by the agribusiness lobby, has portrayed the Brazilian reality and how they were able to forge consensus about its controversial practices and questionable results. By uncovering how their discursive strategy was produced, we aim to verify which facts and arguments have selectively been exposed, and which ones have been excluded, or even shown in a distorted way. The main results show how these entrenched storylines have molded Brazil’s foreign policy.